VALUASI HARGA SAHAM WAJAR PT ASTRA AGRO LESTARI TBK DENGAN METODA FREE CASH FLOW TO THE FIRM - , Priyatno ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis discusses the application of discounted cash flow models to determine the intrinsic value of a share of oil palm plantation company PT Astra Agro Lestari. A top-down approach was taken, starting with an analysis of macroeconomic environment and analysis of the industry in which the company operates. This was followed by an assessment of the company for the financialâs projections for the next five years (2012-2016) to determine the company's intrinsic value. Projected financial statements were analysed using the Free Cash Flow to the firm approach, and were discounted to obtain the value of the firm. Tthe analysis indicated the intrinsic value of equity per share was Rp. 21,638 with the fair price range was Rp. 20.556 - Rp. 22.720. This value compared with the price of the stock of Astra Agro Lestari on the Indonesia Stock Exchange on 29th December 2011 of Rp. 21.700, suggesting that the stock was curently fairvalued.